Upaya Meningkatkan Hasil Belajar Mata Pelajaran Seni Budaya dan Prakarya (SBdP) dengan Memanfaatkan Lingkungan Sekolah - Opida, Seli; Oktaviani, Heriyah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research discusses efforts to improve the learning outcomes of the subject Arts, Culture, and Crafts (SBDP) by utilizing the school environment at SD Negeri 13 Kota Pagaralam. The approach used in this study is descriptive and qualitative. Data collection methods include documentation, observation related to the improvement of learning outcomes in SBdP by utilizing the school environment, and interviews conducted with SBdP teachers about the learning process utilizing the environment, the principal about his role as a leader in managing the educational process at school, and students related to the learning process they undergo in the SBdP subject. The sequential data collection process, data presentation, data verification, and conclusion drawing are part of the data analysis techniques used. The researcher used triangulation techniques, namely time, method, and source triangulation, to ensure data accuracy. Based on the results and discussion, the efforts made in the SBdP learning process at SD Negeri 13 have not been successfully implemented, particularly in grade IV. The teaching methods used by the teachers are still monotonous and tend to be very boring, indicating that the efforts to improve SBDP learning outcomes by utilizing the school environment still require much evaluation.